Standortkonkurrenz von Lebensmittelmärkten. Frühzeitige Abschätzung und Bewertung der Auswirkungen neuer Märkte - Anders, Sascha (Raumforschung und Raumordnung | Spatial Research and Planning, 2018)
The locations of supermarkets and their effects on existing local suppliers are a continuous source of controversial discussion. In the debate among experts how to measure the effects and what actually defines urban development deficits, an objective and comprehensible foundation is missing. Therefore as part of the program „Nachhaltiges Landmanagement“ („Sustainable land management“) of the Bundesministerium für Bildung und Forschung (Federal Ministry of Research and Education (BMBF)) we developed an application-oriented, GIS-based gravity model, which is placed on the anticipated changes in turnover of existing businesses caused by a new supermarket. The appraisal of impacts is achieved with relatively readily available data, the model should, as a rule, work for Germany as a whole. The results can be used as additional assessment at a very early stage, and should give the discussion in the municipalities a better foundation. This paper outlines the difficulties in the judgement of new food markets. It explains the content and methodological background of the developed model, and finally takes a classification of the results.